Evaluation of the accuracy of visual glucose estimates by healthcare providers and patients at Kalafong Hospital, City of Tshwane, South Africa. Issue 1 (2nd January 2020) - Mhishi, Simbarashe B; van Zyl, Danie G
Abstract : Background: A patient-centred approach with self-monitoring of blood glucose (SMBG) has emerged as the preferred approach in monitoring and managing blood glucose. The success of SMBG in diabetes treatment and management relies heavily on the accurate and reproducible measurement of blood glucose values. Aim: To evaluate whether patients and healthcare professionals can accurately estimate blood glucose using photometric strips, by visually matching them to colorimetric charts. Methods: A cross-sectional study design was used with participants enrolled from patients and healthcare providers attending and working at the Diabetes Clinic of Kalafong Provincial Tertiary Hospital (KPTH). A convenience sample of 144 patients and 10 healthcare professionals was enrolled. Results: Limits of agreement of patient and healthcare professional visual estimates were 11.1 to 10.4 mmol/l and 6.7 to 5.7 mmol/l, respectively. The mean difference for estimates by healthcare professionals was 0.8 mmol/l (95% CI 1.30–0.31 mmol/l) while patient estimates had a mean difference of 0.4 mmol/l (95% CI 1.2−0.5 mmol/l). Conclusions: The study noted that visual colour matching was inexact and generally would overestimate blood glucose. Healthcare professionals gave visual estimates that were more accurate in comparison with patients.